Упростить выражение a) (a+b)в квадрате - (a-b)в квадрате=? b) (x+3)(x-2)-3(x-4)=?

0 голосов
21 просмотров

Упростить выражение
a) (a+b)в квадрате - (a-b)в квадрате=?
b) (x+3)(x-2)-3(x-4)=?


Алгебра (22 баллов) | 21 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

***************************************************************************************

(a+b)²-(a-b)²=

=(a+b-(a-b))*(a+b+a-b)=

=(a+b-a+b)*2a=

=2b*2a=

=4ab

***************************************************************************************

(x+3)*(x-2)-3(x-4)=

=x²-2x+3x-6-3x+12=

=x²-2x+6

***************************************************************************************

(127k баллов)